Job satisfaction and social identification among paramedics in southern Poland - Kukla, Paweł; Kózka, Maria; Siemiginowska, Patrycja; Ilczak, Tomasz; Augustyn, Magdalena; Malinowska-Lipień, Iwona (Frontiers in Public Health, 2024)
Introduction. Job satisfaction, based on professional and non-professional factors and individual characteristics of employees, is an important element influencing both the quality of care provided and employee turnover.The study included 137 paramedics employed in field teams and hospital emergency departments. The Job Satisfaction Scale (SSP), the Minnesota Job Satisfaction Questionnaire (MSQ), the Utrecht Work Engagement Scale (UWES), and the Three Dimensional Strength of Group Identification Scale (TSIG) were used to collect the data.The average job satisfaction score measured with SSP in the studied group of paramedics was 24.50. and the average job satisfaction score measured with MSQ was 74.16.The average value of the group identification in the study sample was 61.15. Of the three subscales, the highest scores were obtained in the affect towards the group subscale -22.44, and the lowest in the cognitive centrality subscale -18.78. The analysis showed that job satisfaction positively correlated with social identification (r=0.43) and the ingroup ties (r=0.43), cognitive centrality (r=0.34) and ingroup affect (r=0.37).The surveyed group of paramedics showed moderate job satisfaction (measured with SSP) and work engagement, with a simultaneous high level of job satisfaction (measured with MSQ) and social identification with the professional group. Social identification of studied paramedics varied depending on gender. Women showed higher levels of cognitive centrality, which might mean that they might have had greater need to categorize themselves as paramedics.